2019
DOI: 10.1177/2058738418820402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the transcriptome of circulating immune cells of a New Zealand cohort with myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a poorly understood disease affecting 0.2%–2% of the global population. To gain insight into the pathophysiology of ME/CFS in New Zealand, we examined the transcriptomes of peripheral blood mononuclear cells by RNA-seq analysis in a small well-characterized patient group (10 patients), with age/gender-matched healthy controls (10 control subjects). Twenty-seven gene transcripts were increased 1.5- to sixfold and six decreased three- to sixfold in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 10 publications
(23 reference statements)
3
57
0
Order By: Relevance
“…In recent years ME/CFS research has shifted its focus from attempting to identify a universal ‘causative agent’ for the illness, to instead ascertaining the key affected physiology and biological pathways behind the ME/CFS symptom complex. High-throughput molecular analyses including cytokine production [ 12 ], metabolomics [ 13 16 ], the microbiome [ 17 19 ], epigenetics [ 20 – 23 ], transcriptome [ 24 26 ] and proteome investigations [ 27 – 32 ] have provided substantial evidence of immune/inflammation involvement, and, significantly, suggest there are deficits in energy metabolism and mitochondrial function in ME/CFS. While there have been inconsistencies in the evidence for mitochondrial dysfunction, a growing number of research papers are supportive of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years ME/CFS research has shifted its focus from attempting to identify a universal ‘causative agent’ for the illness, to instead ascertaining the key affected physiology and biological pathways behind the ME/CFS symptom complex. High-throughput molecular analyses including cytokine production [ 12 ], metabolomics [ 13 16 ], the microbiome [ 17 19 ], epigenetics [ 20 – 23 ], transcriptome [ 24 26 ] and proteome investigations [ 27 – 32 ] have provided substantial evidence of immune/inflammation involvement, and, significantly, suggest there are deficits in energy metabolism and mitochondrial function in ME/CFS. While there have been inconsistencies in the evidence for mitochondrial dysfunction, a growing number of research papers are supportive of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent publication has linked organosiloxane contamination to the ever-expanding reports of metabolic and biochemical disruptions inherent to vague syndromes like CFS/ME [17]. The list of metabolic dysregulations and dysfunctional physiology in CFS/ME has now been expanded to include both transcriptome changes and hypothalamic dysfunction [22,23], abnormalities that can easily be caused by the organosiloxane-induced alterations of epigenetic and microglial functions outlined earlier in this report. Chronicity can easily become the norm for all of the above syndromes and illnesses due to (a) Organosiloxane interference with normal healing processes, and (b) The perpetuation of biochemical and epigenetic disruptions during cell division [17,18].…”
Section: Why Does Hpv Vaccine-induced Illness Encompass Numerous Overmentioning
confidence: 96%
“…A transcriptome study of the same ME/CFS and control study group found among genes signi cantly differently expressed in ME/CFS, the three most signi cant and increased were IL8, NFKBIA and TNFAI3P, all functionally related as responders to over-activation of in ammatory NF-KB. STRING (P < 0.01) and ingenuity pathway analysis (P < 0.05) of the biological pathways affected by these changed genes including immune/in ammatory pathways, cellular stress response and oxidative stress, circadian clock function, metabolism and mitochondrial function [26]. The correlating gene transcripts encoding the respiratory complexes, TCA cycle proteins and ATP Synthase subunits were not noted to be signi cantly changed in the ME/CFS transcriptome, so may be regulated by post translational mechanisms to increase their proteins, however similar biological pathways were apparently enriched in both studies.…”
Section: Histone Methylation and Proteasome Activation; Dampened Platmentioning
confidence: 99%
“…Previous studies from our laboratory have used a small cohort of carefully diagnosed ME/CFS patients (the Dunedin cohort) and carried out extensive molecular studies utilizing the principles of precision medicine [33] with strict statistical limits. We have identi ed highly signi cant differences between the patient and control groups [10,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation